2022
DOI: 10.1021/acscatal.2c02579
|View full text |Cite
|
Sign up to set email alerts
|

Designing Cu-Based Tandem Catalysts for CO2 Electroreduction Based on Mass Transport of CO Intermediate

Abstract: Electrochemical reduction of CO2 to high-value hydrocarbons and oxygenates is an attractive technique to store intermittent renewable energy. Diverse catalysts are capable of catalyzing the CO2 to CO conversion, while further reduction of CO occurs almost exclusively on Cu. Monocomponent Cu catalysts suffer from the high overpotential and low Faradaic efficiency of hydrocarbons and oxygenates. Combining CO2 to CO conversion on Au, Ag, single-atom catalysts, etc., with CO reduction on Cu is a promising strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 141 publications
0
53
0
Order By: Relevance
“…The tandem catalyst is to connect a catalyst that efficiently generates CO and a Cu catalyst in series, which can not only promote the conversion of CO 2 to CO but also accelerate the C-C coupling on the Cu catalyst. 88 The efficient transport of CO to Cu catalysts is the key to the design of tandem catalysts. 88 Zhang et al 77 prepared Cu@Ag core-shell nanoparticles with different silver layer thicknesses for the tandem catalysis of CO 2 conversion by generating CO on the Ag shell and further realizing C-C coupling on the Cu core.…”
Section: Cu-based Tandem Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tandem catalyst is to connect a catalyst that efficiently generates CO and a Cu catalyst in series, which can not only promote the conversion of CO 2 to CO but also accelerate the C-C coupling on the Cu catalyst. 88 The efficient transport of CO to Cu catalysts is the key to the design of tandem catalysts. 88 Zhang et al 77 prepared Cu@Ag core-shell nanoparticles with different silver layer thicknesses for the tandem catalysis of CO 2 conversion by generating CO on the Ag shell and further realizing C-C coupling on the Cu core.…”
Section: Cu-based Tandem Catalystsmentioning
confidence: 99%
“…88 The efficient transport of CO to Cu catalysts is the key to the design of tandem catalysts. 88 Zhang et al 77 prepared Cu@Ag core-shell nanoparticles with different silver layer thicknesses for the tandem catalysis of CO 2 conversion by generating CO on the Ag shell and further realizing C-C coupling on the Cu core. The FE values of the total C 2 product, ethylene, and ethanol of the Cu@Ag core-shell nanoparticle catalyst were 67.6%, 32.2%, and 30.4% at −1.1 V vs. RHE, respectively.…”
Section: Cu-based Tandem Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Cu-based tandem schemes have emerged as a valid strategy to enhance the selectivity of CO 2 RR towards multicarbon products (C 2+ ) by decoupling the CO 2 to CO and the CO to C 2+ reduction steps. [6][7][8][9] Previous work has demonstrated that increasing the local concentration of CO and/or the surface coverage of adsorbed CO (*CO) decreases the energetic barrier for C-C coupling, which is the rate-determining step towards C 2+ products on Cu surfaces. [10][11][12][13][14][15][16][17] In addition to their intrinsic catalytic properties (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A way of combining these mass transport effects is by considering geometric catalyst utilization of a CO 2 electrolyzer, which can then be defined as the ratio of the planar catalyst area utilized for CO 2 RR (desired reaction) to the total planar catalyst area present in the system. Recent studies have considered broader mass transport efforts for mapping spatial electrochemical activity and engineering catalyst layers for maximizing multicarbon products from CO 2 RR, but these have yet to be considered as changing in time.…”
mentioning
confidence: 99%